Remaking Muslim Politics - Sean L. Yom (American Journal of Islam and Society, 2007)
We can sense, Robert Hefner announces in the introduction to this edited volume, “a new dynamic of popular participation and contestative pluralism … inspiring dreams of a Muslim politics that is civil and democratic” (p. 11). Herein lies the book’s singular thesis. Since 9/11, scholars have spilled enormous quantities of ink in convincing western audiences that radical violence and ideological intolerance do not characterize mainstream Islam. Yet the quest to delineate Islam’s compatibility with democracy often meant ignoring the complexity of ideas within the stream of democratic Muslim thought. This eclectic collection fills this gap, bringing together twelve authors who demonstrate the rise of new Islamic voices promoting civic pluralism within the boundaries of religious tradition. However, they also show that such views have triggered fierce contestation from more conservative interlocutors. In laying out a sweeping map of these battles, the volume performs a necessary service to general scholars of Islamic politics ...